Between Light and Shadow: Informality in the Russian Labour Market - Vladimir Gimpelson; Rostislav Kapeliushnikov (Institute for the Study of Labor (IZA), 2014)
Economic growth in Russia in the first decade of this century almost doubled the country's GDP but was accompanied by substantial reallocation of labor to the unregulated sector while formal employment was on gradual decline. The paper overviews evolution of the Russian labour market during the period of 2000-10 and discusses most general implications of informality to employment and earnings as well as the associated political economy challenges and consequences.
Keywords: J31; J40; P2; 330; informal labour market; employment; Russia